12 stories about helping the community - Bell, Samantha (Making a difference (12 Story Library (Firm)), 2020)
Showcases twelve organizations that help others in the community. Briefly describes their history and mission, spotlights facts about their work, and features a list of ideas on ways to get involved. Includes a glossary, resources for further reading, and an index.